Konstruksi Wacana Kuliah Gender Lintas Agama di Media Lokal Aceh - Nurrahmi, Febri; Lestari, Fuji (Jurnal Komunikasi Islam, 2017)
This study aims to find out the discourse construction of an interfaith gender lecture published in Serambi Indonesia. Using Van Dijk's discourse analysis model on three news reports during 7-24 January 2015 and on inter-views with three journalists and an editor as well as three readers of Serambi Indonesia, the study concludes that there is a unified discourse found in the elements of text, social cognition and social context which has produced negative impressions towards Rosnida Sari and recovered the image of UIN Ar-Raniry. In short, the news contruction of Rosnida Sari tends to represent her image as a less responsible person and should be academically punished and it reinforces prior discourse depicting her as the cult practitioner.